The making of sports heroes in goalball : the case of visually impaired student-athletes in Kuala Lumpur - Baidruel Hairiel Abd Rahim (AbdulHamid AbuSulayman Kulliyyah of Islamic Revealed Knowledge and Human Sciences,International Islamic University Malaysia, 2022)
Since 1947, goalball sport has been played for rehabilitative purposes among World War veterans and has gained its popularity especially among visually impaired communities around the world. The inception of this sport into the Paralympics has cemented the status of goalball as one of the elite and competitive sports for visually impaired athletes. For many years, studies on goalball were only focusing on the coaching and performing aspects of the sport. The socio-cultural dimensions of goalball sport are often neglected by academias, which prompted the need for sports sociologists and anthropologists to gain more information on the social and cultural aspects of goalball. This thesis aims to explore the engagement of student-athletes with visual impairments in goalball sport. It intends to examine the roles and outcomes of goalball participation among visually impaired student-athletes especially those who play competitively in Kuala Lumpur, Malaysia. It describes how goalball not only serves as the platform for experiences and its benefits for student-athletes, but also to their coaches, peers and family members, especially when the student-athletes complete their secondary education. This study proposes that goalball participation among these students serves as a platform for self-reliance, which is essential for them once they leave school and in producing new sporting heroes among the players. Using a qualitative approach, the study investigates the attributes that the participants gain when they engage in goalball sport. This study recruited 20 participants [N=20] among high profile student-athletes with visual impairments from the categories of B1, B2 and B3 using a purposive sampling technique. The relevant data were obtained qualitatively through in-depth interviews and participant observation over 14 months. The findings reveal that the roles of coaches, family members, peers and senior athletes are substantial to spur goalball sports experiences amongst the players. It is also found that goalball sport is crucial for the survival of the participants as it contributes to (i) self-improvement, (ii) voluntary action, (iii) appreciation, awards and incentives, (iv) prioritising of priorities, (v) determination, (vi) opportunities and (vii) acceptance and sense of belonging, which are indispensable in the making of sporting heroes among them. Using three relevant frameworks of heroism, the power relations discourse and the role theory, this study highlights the specific roles played at all levels and by all actors – from student-athletes with visual impairments to their coaches. This study concludes that goalball provides a platform for student-athletes to create a sense of self-reliance when they complete their secondary education and enter the workforce in the future. Lastly, the thesis provides several recommendations for policymakers, schools, the private sector and the academia as part of an ongoing effort to add to the research discourse in the field of sports for disability, special educational needs and inclusive policy not only in Malaysia but also throughout the world.